Clinical symptoms and conditions leading to metastatic non–small cell lung cancer diagnosis in patients with and without targeted mutations. Issue 28 (1st October 2022) - Apple, Jon; Shah, Anne; Subramanian, Janakiraman; ASLAM, SAAD; Engel-Nitz, Nicole; Weber, Laura A; White, John
Abstract : 401 Background: This study compares patient characteristics, clinical conditions, the prevalence and timing of lung cancer symptoms, and diagnostic procedures from onset to mNCSLC diagnosis for patients with and without targetable mutations. Methods: This was a retrospective claims analysis of Medicare Advantage and commercially insured adult mNSCLC patients (11/01/2012 - 01/31/2020) with continuous health plan enrollment (24 months pre-index and ≥2 months post-index) around the index date (mNSCLC diagnosis). Patients on targeted therapy post-diagnosis were assigned to the targeted group (TG); non-targeted group (NTG) otherwise. Twenty pre-specified lung cancer related symptoms, baseline comorbidities, and diagnostic procedures were examined in the pre-index period. Results: The study comprised 2, 940 patients (TG: 390; NTG: 2, 550); TG had lower mean age (65.8yrs vs 69.2yrs; p < 0.001), more females (59.5% vs 50.6%; p = 0.001), and lower tobacco use (55.9% vs 92.5%; p < 0.001). Mean TG Charlson score was 1.37 in the TG vs 1.93 in the NTG; p < 0.001. There were no significant differences in prevalence of any lung cancer related symptoms (TG 81.8% vs NTG 83.5%; p = 0.4). When comparing the 20 individual, pre-specified lung cancer related symptoms (cough, dyspnea, hemoptysis, etc.), there were also no significant differences between the study cohorts. For patients with symptoms, the mean times from the first symptom to mNSCLC diagnosis were similar (TG: 339.3 days; NTG: 363.1 days; p = 0.13)(Table). There were significant differences in the proportion of patients with comorbidities between study cohorts (TG 64.4% vs NTG 73.5%; p < 0.001). Among patients within TG, there was higher prevalence of pleural effusion (22.1% vs 12.6%; p < 0.001) and lower prevalence of COPD (17.7% vs 50.8%; p < 0.001). For diagnostic procedures, patients in TG had fewer imaging procedures than NTG (Chest x-ray 67.7% vs. 74.1%; p = 0.008, CT scan 57.2% vs 63.5%; p = 0.016, PET scan 19.0% vs 27.1%; p < 0.001); and a longer mean time from first symptom to first imaging procedure (TG: 220 days; NTG: 184 days; p = 0.015)(Table). Conclusions: Patients with and without targetable mutations may differ by some patient characteristics, but they may not differ by presentation and type of lung cancer related symptoms leading up to diagnosis.Temporal outcomes among patients with a baseline symptom. Time to Event (days) Targeted Group (N = 390) Control Group (N = 2, 550) p-value Mean (SD) Mean (SD) Time to index from first symptom date 339.3 (259.5) 363.1 (260.9) 0.128 Time to first imaging procedure from first symptom date 220.0 (249.0) 184.1 (232.4) 0.015 Time to index date from first imaging procedure 182.6 (220.7) 258.7 (257.0) < 0.001 Time to treatment with systemic cancer agent from index 60.6 (82.8) 64.9 (105.2) 0.401 Time to treatment with oral targeted agents from index 159.45 (241.2) – –